2015
DOI: 10.1080/10615806.2015.1085514
|View full text |Cite
|
Sign up to set email alerts
|

Walking versus biofeedback: a comparison of acute interventions for stressed students

Abstract: Biofeedback and Exercise interventions improved emotional states in high-stress college students, but the type of change observed (i.e. energizing, calming or anxiety reducing) depended upon the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 51 publications
0
44
0
2
Order By: Relevance
“…Less is known about the effects of relaxation on fatigue or vigor. Although some studies did not find relaxation to lead to an increase in energetic arousal (Meier & Welch, ; Saklofske et al, ), relaxation was found to increase vigor and decrease fatigue in other studies (Krajewski, Wieland, & Sauerland, ; Sianoja, Syrek, de Bloom, Korpela, & Kinnunen, ). The results of the present study indicate that a relaxation exercise may lead not to an immediate but to a delayed increase in vigor and decrease in fatigue.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Less is known about the effects of relaxation on fatigue or vigor. Although some studies did not find relaxation to lead to an increase in energetic arousal (Meier & Welch, ; Saklofske et al, ), relaxation was found to increase vigor and decrease fatigue in other studies (Krajewski, Wieland, & Sauerland, ; Sianoja, Syrek, de Bloom, Korpela, & Kinnunen, ). The results of the present study indicate that a relaxation exercise may lead not to an immediate but to a delayed increase in vigor and decrease in fatigue.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the relaxation break led to a, albeit slightly delayed, decrease in fatigue. Relaxation is well‐known for its immediate effects on anxiety and tense arousal (Meier & Welch, ; Pawlow & Jones, ). Less is known about the effects of relaxation on fatigue or vigor.…”
Section: Discussionmentioning
confidence: 99%
“…This feedback helps users to learn to improve selfregulation skills through practice in controlling that activity. For instance, the GSR data are used for learning to regulate arousal (Bouchard et al, 2012;Sanchez et al, 2012), the IBI data (Cutshall et al, 2011;Edvardsson et al, 2012) and the RSP data are used for regulating breathing (Adelbach et al, 2012;Wu et al, 2012;Meier and Welch, 2016). The other bio-data are mainly used as secondary information, indicating the results of the biofeedback training.…”
Section: Multimodal Biofeedback (12 Studies)mentioning
confidence: 99%
“…The biofeedback data are displayed on the screen of a personal computer (n = 24) or a mobile/portable device (n = 15). The ambient medium allows the users to receive biofeedback information through the surroundings in a physical Larkin et al, 1992;Goodie and Larkin, 2006;McCraty et al, 2009;Strunk et al, 2009;Cutshall et al, 2011;Henriques et al, 2011;Morarend et al, 2011;Edvardsson et al, 2012;Moraveji et al, 2012;Paul and Garg, 2012;Sanchez et al, 2012;Sutarto et al, 2012;Wells et al, 2012;Wu et al, 2012Wu et al, , 2015Prinsloo et al, 2013;Peira et al, 2014;Whited et al, 2014;Lewis et al, 2015;Pusenjak et al, 2015;Sarabia-Cobo, 2015;Meier and Welch, 2016;Munafò et al, 2016Animations Feijs et al, 2013Al Osman et al, 2016 Visual scene Bouchard et al, 2012;De Jonckheere et al, 2014;Gaggioli et al, 2014;Dillon et al, 2016;van Rooij et al, 2016 Virtual character Chittaro and Sioni, 2014;Arroyo-Palacios and Slater, 2016 Modified game Parnandi et al, 2013;Kotozaki et al, 2014 Ambient light Snyder et al, 2015 Auditory Musical expression Yokoyama et al, 2002;Morarend et al, 2011;Vidyarthi and Riecke, 2013;...…”
Section: Interactive Mediamentioning
confidence: 99%
“…[26] Moreover, shortterm HRVB training reduces anxiety more than walking. [27] There are a specific local changes in brain activity reflecting an increase in internal attention combined with relaxation both during and after this procedure. [28] Thus, analysis of the literature showed the effectiveness of short-term HRVB training with regard to the optimization of autonomic tone and improvement of the functions of central nervous system.…”
mentioning
confidence: 99%